A PtPdCu thin-film catalyst based on titanium nitride nanorod arrays with high catalytic performance for methanol electro-oxidation. Issue 85 (31st August 2016) - Jiang, Shangfeng; Yi, Baolian; Zhao, Qing; Zhang, Hongjie; Su, Yang; Yu, Hongmei; Shao, Zhigang
Abstract : Here, we present a novel MOR anode catalyst based on TiN nanorod arrays with high performance towards MOR. Abstract : Novel thin-film PtPdCu ternary electrocatalysts supported on titanium nitride nanorod arrays (TiN NRs) are fabricated. Unique 3D structures provide an effective way to analyse the influence of catalytic structure on methanol electrooxidation. The PtPdCu–TiN NRs show 1.81- and 2.09-fold greater mass activity than that of PtPd–TiN NRs, and a commercial PtC catalyst, respectively.